A literary examination of electronic meeting system use in everyday organizational life. - McLeod, Poppy Lauretta (Journal of Applied Behavioral Science, 1999)
A study was conducted to examine electronic meeting system (EMS) technology in everyday organizational life by using three famous meetings from popular literature to describe dynamics common in organizational groups. Dysfunctional routines are explored by examining the Mad Hatter's tea party from Alice in Wonderland; social influence in the film Twelve Angry Men; and emotions and symbolism at the biblical event of the Last Supper. The implications of EMS technology use in the dynamics of organizations are discussed. It is concluded that new metaphors are required to guide future EMS research.